The Inflammatory Aspect of Male and Female Pattern Hair Loss - Peyravian N; Deo S; Daunert S; Jimenez JJ (Dove Medical Press, 2020)
Nadia Peyravian,1 Sapna Deo,1 Sylvia Daunert,1 Joaquin J Jimenez1,2 1Department of Biochemistry and Molecular Biology, University of Miami Miller School of Medicine, Miami, FL, USA; 2Dr. Phillip Frost Department of Dermatology & Cutaneous Surgery, University of Miami Miller School of Medicine, Miami, FL, USACorrespondence: Joaquin J JimenezDepartment of Biochemistry and Molecular Biology, Miller School of Medicine, University of Miami, 1011 NW 15th Street, Miami, FL 33136, USATel +1 305 243 6586Email j.jimenez@med.miami.eduAbstract: Male and female pattern hair loss (MPHL and FPHL, respectively), is the most common cause of hair loss affecting nearly 80 million people in the US, yet treatment options remain limited and lacking. As the need for more effective therapeutics remains unmet, this perspective offers a unique angle by directing attention to the inflammatory aspect of MPHL and FPHL. Evidence and implications of inflammation as a characteristic feature of MPHL and FPHL are highlighted through evaluation of clinical and quantitative data. Comparable results suggest the presence of significant perifollicular inflammatory infiltrates, such as lymphocytes and histiocytes, as well as the involvement of inflammatory genes, such as CASP7 and TNF, in the presentation of MPHL and FPHL. Resurfacing of the inflammatory aspect in MPHL and FPHL pathogenesis will advance future developments in MPHL and FPHL therapeutic options.Keywords: hair loss, inflammation, male pattern baldness, female pattern baldness